Transcriptomic Analysis of Rat Cerebral Cortex Reveals the Potential Mechanism of Electroacupuncture Opening Blood Brain Barrier - Ma, Congcong; Gan, Lin; Wang, Hao; Ren, Li; Lin, Yubo; Zhao, Yibin; Zhang, Shanshan; Gong, Peng; Lin, Xianming (Frontiers in Neuroscience, 2022)
Therapeutic treatment options for central nervous system (CNS) diseases are greatly limited by the blood-brain barrier (BBB). Electroacupuncture (EA) can be used to induce an increase in BBB permeability on rats, providing a potential approach for the delivery of drugs from the systemic circulation into the brain. However, there remains a large gap in our knowledge regarding the impact of EA on brain gene expression. This work is focused on investigating the transcriptional changes of rat cerebral cortex following EA and expression changes in genes and bioinformatic analysis was performed. We found that the potential mechanism of EA opening BBB involves receptor-mediated / carrier-mediated endocytosis (RMT / CMT), and related genes include SLC transporter genes and ABC transporter genes. The results also suggested that EA may affect the expression of tight junction (TJ) proteins in endothelial cells by affecting integrin binding, autophagy pathway and calcium signaling pathway, thus further affecting the permeability of blood-brain barrier. Our results provide a valuable resource that will guide mechanism research of EA opening BBB and other ways to mediate drug delivery into the brain.